Complexities and Controversies in Himalayan Research: A Call for Collaboration and Rigor for Better Data - Surendra P. Singh; Rajesh Thadani (Mountain Research and Development, 2015)
The Himalaya range encompasses enormous variation in elevation, precipitation, biodiversity, and patterns of human livelihoods. These mountains modify the regional climate in complex ways; the ecosystem services they provide influence the lives of almost 1 billion people in 8 countries. However, our understanding of these ecosystems remains rudimentary. The 2007 Intergovernmental Panel on Climate Change report that erroneously predicted a date for widespread glacier loss exposed how little was known of Himalayan glaciers. Recent research shows how variably glaciers respond to climate change in different Himalayan regions. Alarmist theories are not new. In the 1980s, the Theory of Himalayan Degradation warned of complete forest loss and devastation of downstream areas, an eventuality that never occurred. More recently, the debate on hydroelectric construction appears driven by passions rather than science. Poor data, hasty conclusions, and bad science plague Himalayan research. Rigorous sampling, involvement of civil society in data collection, and long-term collaborative research involving institutions from across the Himalaya are essential to improve knowledge of this region.